PENGARUH SUBSTRAT IJUK DAN Hydrilla sp. TERHADAP DERAJAT PEMBUAHAN DAN PENETASAN TELUR IKAN MAS - Sinjal, Hengky J (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2011)
Good quality carp seed supply in relation to number, time, price and location is a crucial factor for the success of the fish cultivation. To ensure the availability of fish seed under these requirements, this study was technically directed to increase the fertility rate, the hatchability rte and the survival of larvae and post larvae. This study was aimed to find good substrates for spawning and egg hatching of the common carp, Cyprinus carpio L. Were used at Sugar Palm Fiber and Hydrilla sp. as substrates for the egg attachment. For this, males and females of 1:1 weight ratio were put into the spawning pond. Eggs attached to both susbtrate types were counted. Water quality parameters, such as temperature, dissolved oxygen and pH, were also recorded. Results showed that common carps had higher preference to Hydrilla sp. to attach their eggs than to Sugar Palm Fiber (kakaban). Egg hatching is also higher in Hydrilla sp than in Sugar Palm Fiber (kakaban), even though the degree of conception, however were not significantly different.